EFFECT OF ALTITUDE ON SPIROMETRIC VALUES - Ayub, Mohammad; Daud, Mohammad; Badar, Ahmed; Khan, Farrukh A.; Waqar, Nusrat (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: A total of 132 healthy male subjects from Haripur, Abbottabad and Nathiagali were tested for their lung volumes and flow rates. The spirometric values from Haripur and Abbottabad are comparable to other studies carried out in Pakistan. It was found that there were no significant differences in FEV1 and FEV1 /FVC% of the subjects but the FVC of the subjects from Nathiagali was found to be significantly higher than the lowlanders. Moreover, the rate of decline in the lung volumes and especially the flow rates of the subjects from Nathiagali was higher than the lowlanders. Further insight in the problem is suggested.